Analysis of influencing factors of nurse‐patient disputes based on patient characteristics: A cross‐sectional study - Yawen Wang; Jinjin Lu; Qian Ye; Li Ji; Zhongqiu Lu; Jufang Li; Hongbo Xu (Nursing Open, 2022)
Abstract Aim To explore the prevalence of nurse‐patient disputes and the influencing factors based on an analysis of patient characteristics. Design A cross‐sectional study. Methods This study used the convenience sampling method. Three self‐designed questionnaires based on clinical experience and literature review were used to collect the current status of nurse‐patient disputes and to assess patients’ humanistic qualities and patients’ recognition of nursing work. The Big Five personality questionnaire was used to assess the five personality traits of patients. Results Of the patients, 9.6% reported having a dispute with nurses. The results of binary logistic regression analysis indicated that patients’ humanistic quality, recognition of nursing work and agreeableness in personality traits had a negative predictive effect on nurse‐patient disputes, while family monthly income and neuroticism in personality traits positively predicted disputes.